2018
DOI: 10.26417/ejser.v12i1.p170-176
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Practices of Blended Learning in Foreign Language teaching at USIM

Abstract: 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 7 publications
4
29
1
1
Order By: Relevance
“…This implies that Syrian refugees were satisfied with this system as it took into consideration their personal affairs, and the strength of BL is in its flexibility in dealing with higher education studies. This is in line with several previous related studies like [7], [12], [14], [16], [19], [22], [24]. All of these studies revealed that students who experienced BL have positive perceptions of BL as they were satisfied with the convenience, ease of use, and flexibility of learning.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This implies that Syrian refugees were satisfied with this system as it took into consideration their personal affairs, and the strength of BL is in its flexibility in dealing with higher education studies. This is in line with several previous related studies like [7], [12], [14], [16], [19], [22], [24]. All of these studies revealed that students who experienced BL have positive perceptions of BL as they were satisfied with the convenience, ease of use, and flexibility of learning.…”
Section: Discussionsupporting
confidence: 91%
“…Results revealed that participants who studied using blended learning outperformed those who studies o0nly in a traditional way. Result also showed no effects of the variables of gender and age in determining the perceptions of participants [13], [14], [15], [16]. It can be concluded the research area about blended learning emphasized on students' performance were the prominent research areas about blended learning emphasized students' performance, whereas no study investigated students ' perceptions of the components of blended learning, particularly refugee students at the university level.…”
Section: Blended Learningmentioning
confidence: 83%
See 2 more Smart Citations
“…For teachers, BL helps in improving teaching conditions, offers access to global resources and materials that meet the students' level of knowledge and interest, provides more opportunities for collaboration and meaningful professional development, and improves time efficiency (Ju & Mei, 2018). According to Rubio and Thoms (2014), a BL implementation can empower teachers to respond to a wide variety of students' learning needs, to support learning processes, and to promote active, reflective and collaborative learning.…”
Section: Blended Learning In Efl Contextsmentioning
confidence: 99%